Complex Regional Pain Syndrome Triggered by Snake Bite: Diagnostic Utility of Triple-Phase Single-Photon Emission Computed Tomography-Computed Tomography Bone Scan—Case Report - Ragab, Osama; Alqattan, Haneen; Al Daas, Manar; A. Elrahman, Hany M. (World Journal of Nuclear Medicine, 2025)
Complex regional pain syndrome (CRPS) is a chronic pain disorder with complex pathophysiology involving neurogenic inflammation and autonomic dysfunction. While CRPS is typically associated with trauma or surgery, its occurrence following a snakebite is extremely rare. We report the case of a 47-year-old man who developed persistent pain, swelling, and hypersensitivity in the left foot after a snakebite to the dorsum. Despite prompt administration antivenom and admission to the intensive care unit, the symptoms progressed without systemic infection. Magnetic resonance imaging (MRI) revealed evolving soft tissue inflammation, fat necrosis, and periostitis. Triple-phase bone scintigraphy with single-photon emission computed tomography/computed tomography (SPECT/CT) demonstrated increased perfusion and periarticular tracer uptake consistent with CRPS, while effectively excluding osteomyelitis and abscess. The diagnosis was established using the Budapest criteria, supported by clinical assessment and multimodal imaging, including evidence of evolving periostitis without cortical bone destruction. This case underscores the diagnostic challenge of CRPS in the absence of infection or trauma and highlights the crucial role of MRI and triple-phase bone scintigraphy with SPECT/CT in detecting early osseous involvement and guiding appropriate management.
Keywords: complex regional pain syndrome; snake bite; MRI; bone scan; SPECT/CT